Analysis of Web-Based E-Learning Management System Business Proccess to Increase Learning Effectiveness at SMAABC Bandung - Rosalin Samihardjo; Murnawan; Endang Amalia; Ananda Cipta Pamungkas (Brilliance: Research of Artificial Intelligence, 2023)
The results of the review of the implementation of differentiated learning activities at SMA ABC Bandung which are in accordance with the vision of an independent curriculum based on a digital school as well as the diverse characteristics of students at SMA ABC Bandung support the development of a digital technology-based learning management system with the E-Learning Management System of SMA ABC Bandung which is built in 2020 in line with the LFH (Learning From Home) learning scheme. This supports innovation and creation in the development of digitalization-based learning in this school. This research aims to evaluate the design of E-Learning products that use Moodle as a platform, with a focus on the product's ability to increase the effectiveness of differentiated learning at SMA ABC Bandung. This research uses a Research and Development approach with a one group pre-test post-test design. The samples for this research were students in classes X, XI, XII and several ELearning Management System operators at SMA ABC Bandung. Based on the results of the existing design analysis, it can be seen and concluded that the ELearning Management System application for SMA ABC Bandung has good effectiveness. In this way, it can be utilized effectively by all school components that use it.